Smoking Cessation Intervention in a Cardiovascular Hospital Based Clinical Setting - Samaan, Zainab (Hindawi Publishing Corporation, 2012)
Introduction. Smoking is a leading cause of morbidity and mortality globally and it is a significant modifiable risk factor for cardiovascular disease (CVD) and other chronic diseases. Efforts to encourage and support smokers to quit are critical to prevent premature smoking-associated morbidity and mortality. Hospital settings are seldom equipped to help patients to quit smoking thus missing out a valuable opportunity to support patients at risk of smoking complications. We report the impact of a smoking cessation clinic we have established in a tertiary care hospital setting to serve patients with CVD. Methods. Patients received behavioural and pharmacological treatments and were followed up for a minimum of 6 months (mean 541 days, SD 197 days). The main study outcome is ≥50% reduction in number of cigarettes smoked at followup. Results. One hundred and eighty-six patients completed ≥6 months followup. More than half of the patients (52.7%) achieved ≥50% smoking reduction at follow up. Establishment of a plan to quit smoking and use of nicotine replacement therapy (NRT) were significantly associated with smoking reduction at followup. Conclusions. A hospital-based smoking cessation clinic is a beneficial intervention to bring about smoking reduction in approximately half of the patients.